2011
DOI: 10.1007/s11434-011-4858-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between composite structures and compressive properties in CuZr-based bulk metallic glass system

Abstract: Bulk metallic glass (BMG) composites with the austenite B2 phase as reinforcement macroscopically showed strain hardening behavior due to the plasticity induced by martensitic transformation during deformation. Relationship between characteristics of the B2-CuZr reinforcing phase and uniaxial compressive properties of CuZr-based BMG composites was studied. Mechanical properties of these BMG composites were found to depend on not only the reinforced phases but also the amorphous matrix, and the yield and fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…(b) The present composites are superior in tensile properties among various BMG composites in different systems ductilized by different crystalline phases68910112224282930313233.…”
Section: Figurementioning
confidence: 84%
“…(b) The present composites are superior in tensile properties among various BMG composites in different systems ductilized by different crystalline phases68910112224282930313233.…”
Section: Figurementioning
confidence: 84%
“…For example, CuZr-based BMG composites with different sample sizes containing minor element additions such as Al, Ti, Ag, Ni, Co, Y, Er, V, W, or Ta have been successfully fabricated [20][21][22][23][24][25][29][30][31][32][33][34][35][36][37]. Two key requirements should be satisfied for the fabrication of CuZr-based BMG composites: (1) maintaining sufficiently high glass-forming ability (GFA) in order to fabricate large-sized BMG composites [20][21][22][23][24][25][29][30][31][32][33][34][35][36][37]; and (2) stabilization of metastable B2 CuZr phase in order to suppress its decomposition into equilibrium phases (EPs) [29][30][31][32][33][34]. Previous results [22,38] demonstrated that minor Co addition to CuZr alloys can dramatically enhance the thermal stability of the B2 CuZr phase but gravely deteriorate the GFA of CuZr-based alloys.…”
Section: Introductionmentioning
confidence: 99%
“…It was known that yield strength and Young's modulus of composite materials can usually be estimated from properties of the constituent phases by the -rule of mixtures (ROM)‖ principle. Based on the yield strength of the monolithic amorphous matrix and pure B2-CuZr phase[26,27], the estimated values of these BMG composites are also shown as the dashed line in…”
mentioning
confidence: 99%